In hindsight: the challenges of virtual mentoring the future higher education leaders of Afghanistan - Victoria Lindsay (International Journal of Evidence Based Coaching and Mentoring, 2014)
This article, written in hindsight, is a personal account of a British Council and Afghan Ministry of Higher Education project that sought to establish mentoring relationships between the next generation of leaders in Afghanistan and volunteers from UK higher education. Several learning points have emerged: the need for a simple programme design; the inappropriateness of mentoring to develop management and leadership skills at this time; a desire to formalise inputs; a necessity for face-to-face input and the difficulties of establishing mentoring relationships virtually. These findings contribute to understanding of the difficulties of implementing virtual mentoring within a challenging post-conflict environment.